2007
DOI: 10.1063/1.2816214
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction in undoped ultrananocrystalline diamond thin films and its dependence on chemical composition and crystalline structure

Abstract: Ultrananocrystalline diamond film deposition by direct-current plasma assisted chemical vapor deposition using hydrogen-rich precursor gas in the absence of the positive columnInteresting trends in direct current electrical conductivity of chemical vapor deposited diamond sheetsThe electrical conduction behavior of undoped ultrananocrystalline diamond ͑UNCD͒ and its dependence on deposition temperature and chemical structure are presented. UNCD films were grown using a microwave plasma-enhanced chemical vapor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Overall the implanted nitrogen enhances the field emission properties of UNCD even after post-implantation annealing as reported by Joseph et al 10 Several mechanisms have been proposed to explain the observed field enhancement behavior, while no single mechanism alone could give a complete picture. 10,[13][14][15][16][17][18][19] To understand the enhancement of field emission in nitrogen implanted UNCD samples further, Raman, XPS, TEM, STM, and STS measurements have been carried out in more detail. STS in CITS mode is used to confirm the emission sites in the nitrogen implanted UNCD samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the implanted nitrogen enhances the field emission properties of UNCD even after post-implantation annealing as reported by Joseph et al 10 Several mechanisms have been proposed to explain the observed field enhancement behavior, while no single mechanism alone could give a complete picture. 10,[13][14][15][16][17][18][19] To understand the enhancement of field emission in nitrogen implanted UNCD samples further, Raman, XPS, TEM, STM, and STS measurements have been carried out in more detail. STS in CITS mode is used to confirm the emission sites in the nitrogen implanted UNCD samples.…”
Section: Resultsmentioning
confidence: 99%
“…Our results support the possibility of a grain-boundary electron transport mechanism (conductivitychannel process). [13][14][15] Even though CITS observations show that grain boundaries are the prominent electron emission sites at the nitrogen fluence of 5 Â 10 15 ions=cm 2 , I-V curves show that emission is also coming from the grains but at a higher turn-on field. If the nitrogen ion fluence is increased further, sp 2 content and the density of states at the grains are expected to increase proportionally, and band structure will show metallic behavior like that of grain boundaries, and the grains may not remain purely as diamond.…”
Section: (A)mentioning
confidence: 87%
“…3 During the growth of diamond films, hydrogen is usually incorporated into the materials and is presumed to reside at the grain boundaries. 4 Studies have been conducted on the correlation of hydrogen retention with the bonding, 4-6 conductivity, 7 and field emission 8,9 of diamond films. However, the control of hydrogen content in the diamond films is complicated.…”
Section: Effect Of Gigaelectron Volt Au-ion Irradiation On the Characmentioning
confidence: 99%
“…On the other hand, the sp 2 -bonded carbon within chemical vapor deposited ͑CVD͒ diamond films can be thought of as a conduction promoter, particularly if the sp 2 -bonds form interconnected networks along which electrons are free to move. 4 Control of the proportion of sp 2 -bonds can be achieved by the irradiation of energetic heavy ions into the diamond thin films. Many reports have discussed the effects of ion beam irradiation on the characteristics of type IIa diamond, 10 diamondlike carbon films, 11 taC, 12 , graphite, 13 and polycrystalline CVD diamond films.…”
Section: Effect Of Gigaelectron Volt Au-ion Irradiation On the Characmentioning
confidence: 99%
“…Much work has been carried out to improve the field emission of microcrystalline and nanocrystalline diamond by the ion implantation process. 10,11 Moreover, many reports have discussed the effects of ion beam irradiation on the characteristics of carbon based materials such as type IIa diamond, 12 diamond-like carbon films, 13 taC, 14 graphite 15 and polycrystalline CVD diamond films. [16][17][18] Furthermore, Pandey et al 19 and Koinkar et al 20 have studied the field emission enhancement by swift heavy ion irradiation in CVD diamonds; nevertheless, the mechanism for the modification of these characteristics remains unclear.…”
Section: Introductionmentioning
confidence: 99%